Putting the “Return” Back in the Inhibition of Return Effect in Working Memory - Caro Hautekiet; Naomi Langerock; Evie Vergauwe (Journal of Cognition)
The inhibition of return effect in perception refers to the observation that one is slower to re-attend a location that was attended right before, compared to a location that was not attended right before. Johnson et al. (2013, Psych. Sc., 24, 1104–1112, doi:10.1177/0956797612466414) observed a similar inhibitory effect for an attended item in working memory, which the authors referred to as an inhibition-of-return-like effect. However, testing an inhibition of return effect requires attention to be disengaged from the attended item, before testing whether participants are slower to return to said item. This was assumed but not experimentally manipulated in the paradigm by Johnson and colleagues. In the current study, we investigated whether an inhibition of return effect can be observed in working memory when attention is experimentally disengaged from the attended item before measuring whether responses are slower for the item in question. Participants were indeed slower to respond to a memory probe that matched the item that was attended right before, compared to a memory probe that matched the item that was not attended right before. Thus, our test with more experimental control did result in an inhibition of return effect in working memory.